Study on the Compromise Effect Under the Influence of Normative Reference Group - Du, Qinglong; Li, Kunyang (Frontiers in Psychology, 2022)
Compromise effect is an important context effect, but its research is still insufficient under the influence of social factors and purchase tasks. This study explores the change of compromise effect in different group norm scenarios by constructing three different group norm reference point. Three conclusions were drawn. First, the compromise effect always exists under the influence of different groups’ normative reference point if there is a compromise effect in a product set. Second, the effect value of compromise effect will be significantly different with the change of group norm reference point. Third, group norms can indeed induce the compromise effect. Therefore, these findings would help to further enrich the literature results of the compromise effect and strengthen its application in marketing practice.